PERANCANGAN TAMPILAN APLIKASI DOMPET DIGITAL BERBASIS MOBILE DENGAN PENDEKATAN HUMAN-CENTERED DESIGN - Md Wira Putra Dananjaya; Putu Gita Pujayanti (Universitas Lampung, 2024)
This research aims to design and develop the user interface of a mobile-based digital wallet application using the Human-Centered Design (HCD) approach. The HCD method is employed to prioritize user needs and preferences in the application interface development. The application prototype includes features such as transaction tracking, budget management, and financial reporting, with the goal of enhancing the user experience in personal financial management. The development process involves design iterations based on user feedback to ensure the interface aligns with user expectations and needs. Usability testing results using the System Usability Scale (SUS) indicate a positive score of 75.6, signifying good acceptance of the application interface. The practical implications of this research are to provide more effective design guidelines for the development of digital wallet applications that consider user comfort and needs.